Análise de métodos para estimação da velocidade no eixo de motores de indução trifásicos - Lyra, Gabriela Jordão (2014)
The three phase induction motor (MIT) is the main system in electromechanical conversion, present in practically all industrial processes. Due to its versatility and low cost, the use of frequency inverters combined with MIT practically replaced the DC motors in systems requiring variation in angular velocity. For closed-loop control at MIT, without the use of speed sensors (sensorless), it is essential to estimate the velocity on the axis with high accuracy and with satisfactory response time. The proposed work has the object of analyzing different methods that can be employed to estimate the speed in sensorless axis, named according to their fundamental principle, they are: the method of harmonic slots, the torque in the air gap and the acoustic emission. The first mentioned is the best known non-invasive method in the state art, the second one was recently developed in the laboratory and the third one was exhibited here for the first time. All methods are compared with a reference instrument for measuring speed (tachometer). In order to obtain validation of the techniques we constructed a work bench tests basically composed by a three phase induction motor, torque meter and DC motor used as a generator (to enforce the axis load variable). The main objective of the study is to compare the methods for various situations of speed and load, also based on the degree of invasiveness and accuracy of each method. For the development and analysis of technique for harmonic slots and acoustic emission, a spectral analysis by Fourier transform of the current signal and the sound was performed, respectively. It was used tools such as MATLAB and LABVIEW for the computational study. After extensive experimental testing, the methods have been validated and it was obtained conclusions about different aspects of each discussed technique.